THE STUDY OF PLANES TANGENT TO THE CYLINDRICAL SURFACES - Sanda Bodea (Journal of Industrial Design and Engineering Graphics, 2017)
Taking into account the practical utility of the surfaces of rotation, work proposes the study of the methods of resolution and the determination of the tangent to it, regarding the cylindrical surfaces. The planes tangent taken in the study shall be determined under certain conditions imposed, using knowledge of descriptive geometry.